(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The treatment of noncommunicable diseases (NCDs) such as coronary heart disease and type 2 diabetes mellitus drives up health-care expenditures. Physical exercise is thought to lower the chance of developing certain illnesses. Cross-sectional research revealed that physical exercise is linked to improved health and that it may help to avoid the development of certain illnesses. The goal of this study is to synthesize the available data regarding the long-term (>5 years) link between physical activity and weight gain, obesity, coronary heart disease, type 2 diabetes, Alzheimer’s disease, and dementia. Using digital databases, fifteen longitudinal studies with at least 5-year follow-up periods and a total of 288,724 individuals (>500 participants in each study) aged 18 to 85 years were found. Only studies involving healthy people at baseline, purposeful physical activity, and the specified NCDs that were published in English were included. The findings of these research indicate that physical exercise has a long-term beneficial effect on a variety of illnesses. There are few long-term research on the connection between physical activity and the occurrence of NCDs, according to this review.